Numbers of Follicles, Pregnancy, Expression of Reactive Oxygen Species (ROS), and Ovarian Genes in Sheep Treated with Vitamin E, L-Carnitine, and Fish Oil - M. Hatami; H. M. Yarahmadi; J. Fakhraei; A. Ahmadi (Faculty of Animal Science, Bogor Agricultural University, 2022)
This study was performed to evaluate the effects of vitamin E, L-carnitine, and fish oil on the numbers of follicles, pregnancy, Reactive Oxygen Species (ROS) expression, and expression of several ovarian genes in sheep. For this purpose, 256 sheep were randomly divided into eight experimental groups. They were given a diet supplemented with vitamin E, L-carnitine, and fish oil alone and in combination. FBS, estradiol levels, size of the follicles, and pregnancy rate were observed. Expressions of Superoxide Dismutase 1 (SOD1), Superoxide Dismutase 2 (SOD2), Transforming Growth Factor –β (TGF-β), and Peroxisome Proliferator-Activated Gamma Receptor (PPAR-γ) genes were measured using Reverse Transcription-Polymerase Chain Reaction (RT-PCR), and ROS was measured using fluorescence microscope. At the time of mating and pregnancy, the highest number of follicles and pregnant ewes were observed in the groups supplemented with fish oil and antioxidants (p<0.01). The lowest numbers of follicles and pregnancy was observed in the group supplemented with fish oil alone (p<0.01). The highest expressions of SOD1 and TGF-β genes (p<0.01) as well as SOD2 and PPAR-γ (p<0.05) were observed in the group of concomitant use of fish oil with antioxidants. The highest amount of ROS was found in fish oil group (p<0.01), and the lowest was found in the groups supplemented with fish oil and antioxidant (p<0.01). The use of fish oil along with vitamin E and L-carnitine improved follicle function and increased pregnancy rate by reducing ROS in ewes’ ovaries as well as increasing the expression of SOD1, SOD2, TGF-βRI, and PPAR-γ genes. The use of fish oil along with antioxidants increases follicles and improves fertility in sheep.